Determining the probability of radioactive materials on properties in Monticello, Utah - Wilson, M J; Crutcher, J W; Halford, D K (Health physics (1958), 1992)
The former uranium mill site at Monticello, UT, is a surplus facility subject to cleanup under the Surplus Facilities Management Program. Surrounding properties contaminated with mill site material are also subject to cleanup and are referred to as Monticello Vicinity Properties. The objective of this study was to determine the probability that a vicinity property not addressed under the Monticello Vicinity Properties project could contain Monticello mill-related residual radioactive material in excess of Department of Energy guidelines. The study was conducted in a short time frame to protect public health. Statistical methods were used to select 48 random properties for radiological screening surveys. Results of this study may be used to predict the potential number of unassessed properties (results suggest approximately 20%) that contain radioactive contamination that exceeds Department of Energy guidelines and will require remedial action.